Application of New Sero- Diagnostic Techniques and Molecular Assays to Characterize Recent Mycoplasma Isolates from Ruminants in Nigeria (NTU Journal of Agriculture and Veterinary Science, 2025)
This study investigated the presence of contagious bovine pleuropneumonia (CBPP) and contagious caprine pneumonia (CCPP) in ruminants to confirm and identify the mycoplasma species present. A comprehensive approach was employed, involving serological and molecular assays. A total of 342 cattle and 319 goats were tested, with 42 cattle and 23 goats showing positive serum samples, along with six stored cultures. These samples were analyzed using various serological assays, including IDEXX CBPP and CCPP cELISAs, Immunoblot, CapriLAT, BoviLAT, and the Complement Fixation Test (CFT). Molecular techniques such as PCR-DGGE, species-specific PCRs, and real-time PCR kits were also utilized. The results indicated serological evidence of CCPP and CBPP infections, with some samples positive for M. agalactiae and M. ovipneumoniae. Due to culture contamination, the  real-time PCR results were often borderline. However, the study suggests mixed infections in goats and highlights the importance of storing purified colony isolates and expanding sampling regions to identify diagnostic biomarkers and potential vaccine traits for mycoplasmas in Nigerian isolates.